An improved ultrasonic method for plane stress measurement using critically refracted longitudinal waves. (October 2018) - Wang, Wei; Xu, Chenghai; Zhang, Yumin; Zhou, Yufeng; Meng, Songhe; Deng, Ya
Abstract: An improved ultrasonic method was developed theoretically and experimentally for plane stress measurement using critically refracted longitudinal (LCR) waves. Cruciform specimen method, combined with a digital image correlation (DIC) method, was applied to confirm the validity of this method. Based on the acoustoelastic theory, LCR waves with arbitrary detection directions were considered and relations between time-of-fight and biaxial principal stresses were described. To generate the LCR wave in cruciform specimen, a regular octagon polymethyl-methacrylate (PMMA) wedge was designed in accordance with Snell's law. Finally, validation experiments were performed under different step loads using cruciform specimens. In these experiments, the strain fields of cruciform specimens were extracted by DIC method and used to calculate the reference values of plane stress. By comparing the measured principal stresses with the reference values, the validation and precision of the improved ultrasonic method presented in this work were demonstrated. Graphical abstract: Image Highlights: An improved ultrasonic method for plane stresses measurement is proposed. The validity of this method was confirmed by cruciform specimen method. Experiments were designed combining the cruciform specimen with the DIC method. The uniformity of the region of interest was evaluated using the DIC method. The results of ultrasonic method were compared with the reference values.